2018
DOI: 10.5897/ajb2017.16333
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum spp. potential for maize growth and yield

Abstract: The importance of biotechnology involved in the availability of nutrients to plants in different production systems is well known. In the search for agricultural sustainability, biological nitrogen fixation process stands out, especially in tropical regions where soil organic matter can be rapidly mineralized. In this aspect, researches have pointed out the potentialities of the use of diazotrophic bacteria, as well as other growth-promoting bacteria in Poaceae. Maize crop, especially, stands out in the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Just as with the previous phytohormones, gibberellins produced by PGPRs are considered as stimulators of plant growth and development. As reported by Lucas et al [78], the increase in GA3 levels in roots and boosting their growth has been related to Azospirillum strain inoculation in maize roots.…”
Section: • Gibberellinsmentioning
confidence: 57%
“…Just as with the previous phytohormones, gibberellins produced by PGPRs are considered as stimulators of plant growth and development. As reported by Lucas et al [78], the increase in GA3 levels in roots and boosting their growth has been related to Azospirillum strain inoculation in maize roots.…”
Section: • Gibberellinsmentioning
confidence: 57%
“…Although not yet elucidated, beneficial effects resulted from PGPR producing phytohormones are exerted in different plant species, such as maize (Lucas et al, 2018), rice (Lee et al, 2015), or soybean (Kang et al, 2019).…”
Section: Prominent Mechanisms Of Pgpr-mediated Alleviation Of Abiotic...mentioning
confidence: 99%
“…The literature review indicated that the Azospirillum spp. is associated with biological nitrogen fixation, phosphate solubilization, and plant protection against abiotic stress [10,11].…”
Section: Introductionmentioning
confidence: 99%